2020
DOI: 10.20870/ijvr.2020.20.1.3183
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of locomotion techniques in virtual reality

Abstract: This study represents a systematic literature review in which we explored the locomotion techniques in virtual reality between 2012 and 2019. We analysed and compared 22 locomotion methods that we have identified in 26 papers included in our review. The objective is to better understand relevant locomotion techniques and their impact on the user experience. The review of the literature has shown a wide range of different locomotion techniques which each technique is characterized by different advantages and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Nilsson et al [20] employed the two previously-proposed LT distinctions to create a taxonomy based on three orthogonal dimensions: (i) whether the user is stationary or performs physical movement (user mobility, as proposed by [6,28]), (ii) whether the technique involves a virtual vehicles or not (source of virtual motion), and (iii) whether the techniques qualify as mundane or magical (metaphor plausibility, as proposed by [23]). Cherni et al [10] proposed a taxonomy to distinguish three main categories of LTs according to whether they were centered on the user body, external peripheral device, or both. The body-centered techniques were further divided into leaning vs. stepping LTs, while the peripheral LTs were subdivided into semi-natural vs. non-natural techniques.…”
Section: Taxonomies and Attributes Of Ltsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nilsson et al [20] employed the two previously-proposed LT distinctions to create a taxonomy based on three orthogonal dimensions: (i) whether the user is stationary or performs physical movement (user mobility, as proposed by [6,28]), (ii) whether the technique involves a virtual vehicles or not (source of virtual motion), and (iii) whether the techniques qualify as mundane or magical (metaphor plausibility, as proposed by [23]). Cherni et al [10] proposed a taxonomy to distinguish three main categories of LTs according to whether they were centered on the user body, external peripheral device, or both. The body-centered techniques were further divided into leaning vs. stepping LTs, while the peripheral LTs were subdivided into semi-natural vs. non-natural techniques.…”
Section: Taxonomies and Attributes Of Ltsmentioning
confidence: 99%
“…Existing review papers mainly rely on academic publications in their analysis and rarely consider the rapidly growing number of techniques that are proposed by the industry practitioners. As an example, Cherni et al [10] observed that the majority of the techniques utilized the leaning-based subdivision of the user body-centered category in their taxonomy. The high frequency of leaning-based LTs is likely due to the choice of focusing on scientifc literature, which does not necessarily refect user preference and mass adoption.…”
Section: Taxonomies and Attributes Of Ltsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cherni et al [29] explored locomotion techniques in VR between 2012 and 2019. Several studies applied body motion for locomotion to enhance spatial perception and user experience, which increases the sensation of one's own selfmotion.…”
Section: Motion-based Locomotionmentioning
confidence: 99%
“…They might not have the necessary infrastructure in place to properly embrace the VR-based training. However, it is worth highlighting that despite technological, pedagogical, and organisational challenges, VR based training has gained a keen interest in both educational and industrial communities (Chien et al, 2020;Dubovi et al, 2017;Gao et al, 2019;Virvou & Katsionis, 2008) and several studies have proposed solutions to effectively tackle these challenges (Cherni et al, 2020;Mikropoulos & Natsis, 2011;Qin et al, 2010). From a VR system design standpoint, the relationship between learning content and choice of design elements plays a central role in supporting VR-based learning (Radianti et al, 2020), providing a detailed overview of suitable design elements, such as moving around and realistic surrounding to train for procedural practical knowledge.…”
Section: Challenges Of Designing Virtual Learning Environmentsmentioning
confidence: 99%